EDUKASI PUBLIC SPEAKING MENGENAI AYO BICARA BAIK PADA ANAK BINAAN PKBM JICT - Pramelani, Pramelani; Latuperissa, Anggie Ayu Astria; Sejati, Taqwa; Fajar, Adityo (ABDI MAKARTI, 2024)
Community service is an activity carried out by lecturers and students. This activity was created to overcome problems discovered by PKBM JICT partners who have been assisting children who study at home so they can study at the same level as in formal schools. These children drop out of school because they are unable to continue to formal school. The presence of PKBM JICT really helps children who have dropped out of school. In communicating well, the couple's children have never gained knowledge about public speaking. Therefore, lecturers and students raised the theme of public speaking community service "Let's Talk Well". The methods used are pre-service, implementation and evaluation methods. As a result, this activity is very beneficial for the children assisted by PKBM JICT in how to speak well so that it can be useful in everyday life. JICT PKBM partners also asked for a similar event to be held again.